Factors influencing quality variation in cocoa (Theobroma cacao) bean flavour profile — A review. (April 2016) - Kongor, John Edem; Hinneh, Michael; de Walle, Davy Van; Afoakwa, Emmanuel Ohene; Boeckx, Pascal; Dewettinck, Koen
Abstract: This review examined the factors that influence flavour volatiles of cocoa beans and the volume of work that needs to be done on these factors and their impact on the flavour volatiles of commercial cocoa beans. Cocoa bean flavour is one of the most important quality attributes as flavour is central to acceptability of cocoa beans and cocoa products such as chocolate. The complex composition of cocoa bean flavour depends on bean genotype, postharvest treatments such as pulp pre-conditioning, fermentation and drying, industrial processes such as roasting as well as the type of soil and age of cocoa tree. The bean genotype determines the chemical composition of the bean, specifically the contents of bean storage proteins, polysaccharides, and polyphenols. This determines the quantities and type of precursors formed during fermentation and drying processes leading to flavour formation, hence, influencing both flavour type and intensity. Cocoa bean fermentation and drying result in the breakdown of the storage proteins by endogenous proteases into amino acids and short chain oligopeptides while the polysaccharides are also degraded by invertase to glucose and fructose. The amino acids, oligopeptides, glucose and fructose react with each other during the roasting process to produce the typical cocoa flavour volatiles. Polyphenols are also oxidized by polyphenol oxidase during fermentation and drying which reduce the astringency and bitterness of the beans, thus, enhancing the flavour of cocoa beans. However, the extent to which other factors such as age of the cocoa tree and soil chemical compositions influence the formation of flavour precursors and their relationships with final flavour quality remains unclear. With increasing demand for sustainable production of high quality cocoa beans, greater understanding of factors contributing to the variations in flavour character would have significant commercial implications. Highlights: Cocoa beans flavour determines acceptability of cocoa beans and cocoa products such as chocolate. It is influenced by type of cocoa, soil chemical compositions, age of cocoa tree, postharvest treatments and roasting. There is research gap on impact of cocoa tree age and soil chemical compositions on formation of flavour volatiles.